LINGUO-CULTURAL SITUATION IT IS LINGUO-CULTURAL CONCEPTS - Akhmedova Shakhodat Makhmutovna (Journal Park Publishing, 2024)
The the article is to characterize verbalization of the figurative component of the linguocultural concept in the linguo-cultural situation.
Keywords: a linguo-cultural situation, linguo-cultural concepts, modeling, paradigmatic, theoretical analysis verbalization.